Universal Emergence of Precore Mutant Hepatitis B Virus along with Seroconversion to Anti-HBe Irrespective of Subsequent Activity of Chronic Hepatitis B - Koh, Kwang Cheol (Korean J Intern Med, 1994)
OBJECTIVES: It has been controversial whether or not the emergence of precore mutant HBV is related to the severe form of chronic hepatitis B (CH-B). To further clarify the role of the precore mutant HBV in the natural course of CH-B, we conducted a longitudinal analysis of precore-region sequences according to the biochemical severity along with seroconversion to anti-HBe in patients with CH-B. METHODS: The precore sequences of the ten sets of serial serum samples, obtained from 6 chronic hepatitis B patients with (group I) and from 4 patients without subsequent biochemical remission after seroconversion to anti-HBe (group II), were analyzed by direct sequencing of DNA amplified by PCR. RESULTS: The precore mutat HBV having a G-A mutation at the nucleotide 1896 was most commonly found (9/10). Wild-type precore HBV was detected in 4 of 6 (66.7%) in group I and 3 of 4 (75.0%) in group II during HBeAg-positive period (p >0.05), and during anti-HBe-positive period it was found in 2 of 6 (33.3%) in group I and 0 of 4 (0%) in group II (p >0.05). In contrast, precore mutant HBV was detected in 5 of 6 (83.3%) in group I and 2 of 4 (50.0%) in group II during HBeAg-positive period (p >0.05), and in all patients of both groups during anti-HBe-positive period. CONCLUSION: The most common type of precore mutant HBV in Korea was the mutant with a G-A mutation at nucleotide 1896. The emergence of precore mutant HBV was a universal phenomenon during the natural history of CH-B; therefore, the precore mutant does not appear to have an pathogenic role in determining the severity of the CH-B.